نمذجة وتحليل مقبض روبوت ثنائي الفكوك مقاد بواسطة مشغل خطي وحيد - حبيب, ربيع; ساعي, مريم; دبور, عبد الرزاق (Latakia University Journal -Engineering Sciences Series, 2018)
Grippers are important parts of industrial robots which allow pick up objects and moving them to specified place. This paper presents an analysis study of two jaw gripper controlled by a single linear actuator. At first, mathematical model which describes gripper’s jaw displacement and applied force by actuator rated to force should be applied to the target object has been concluded, also the values of the stresses that are exposed in the gripper’s jaws when target object caught with 50N force when manufactured from different materials have been found and the validity of the mathematical model has been tested on objects with different sizes and materials depending on Solidworks. The movement of the gripper’s jaws was also analyzed during object pick up to find control signals (position, speed, acceleration) should be applied to perform pick up task correctly thus finding the specifications should be provided in the linear actuator. تشكل المقابض جزء مهم من الروبوتات الصناعية بحيث تسمح بالتقاط أجسام ونقلها إلى مكان محدد. يقدم البحث دراسة تحليلية لمقبض ثنائي الفكوك متحكم به بواسطة مشغل خطي وحيد. بداية تم استنتاج النموذج الرياضي الذي يصف مقدار إزاحة فكي المقبض والقوة الواجب تطبيقها من قبل المشغل الخطي نسبة إلى القوة الواجب تطبيقها على الجسم الهدف, كما تم ايجاد قيم الحدية للإجهادات التي يتعرض لها فكي المقبض عند التقاط الجسم الهدف بقوة تبلغ (50N) وذلك عند تصنيعه من مواد مختلفة, واختبار صحة النموذج الرياضي على أجسام ذات أحجام ومواد مختلفة وذلك بالاعتماد على برنامج Solidworks. كما تم تحليل حركة المقبض أثناء عملية التقاط الجسم الهدف وذلك لإيجاد إشارات التحكم (موضع وسرعة وتسارع) الواجب تطبيقها لتنفيذ عملية الالتقاط بشكل صحيح وبالتالي ايجاد المواصفات الواجب توفرها في المشغل الخطي.